Modeling of dose-response relationships between Pb and Cd levels in testicular and prostate cancer tissues and testosterone levels - Javorac, Dragana; Baralić, Katarina; Marić, Djurdjica; Antonijević Miljaković, Evica; Andjelković, Milena; Ćurčić, Marijana; Djukić-Ćosić, Danijela; Bulat, Zorica; Antonijević, Biljana; Mandić Rajčević, Stefan; Aćimović, Miodrag; Buha Djordjević, Aleksandra (Archives of Pharmacy, 2022)
Exposure to lead (Pb) and cadmium (Cd) poses risk to human health. It is known that these metals have toxic impact on male reproductive system, leading to physiological disorders and infertility. Limited data indicates the carcinogenic potential of Pb, while Cd has been recognized as carcinogen. Benchmark dose-effect modeling can be applied to data from human, animal and ecotoxicological studies with the aim to obtain Benchmark dose (BMD), starting point in human health risk assessment. The aim of this study was to use Benchmark modeling to determine the dose-effect relationship between Pb and Cd levels in tissues of testicular and prostate cancer patients and serum testosterone levels. The study was conducted at the Clinical Center of Serbia, and included 104 patients with prostate and testicular cancer. Cd and Pb levels (ng/g) were measured by atomic absorption spectrophotometry in isolated healthy surrounding and carcinoma-affected tissues. Testosterone levels (ng/mL) were measured using the chemiluminescence immunoassay (CLIA) method. Dose-effect modeling was performed using PROAST70.1 software with continuous data. The dose dependence was obtained between Cd levels in tumor tissue and testosterone levels (BMD: 0.0024 ng Cd/g, prostate cancer and 0.0038 ng Cd/g, testicular cancer). Dose dependence was obtained between Cd levels in healthy surrounding tissue and testosterone levels (BMD: 0.0092 ng Cd/g). No dose dependence was obtained when modeling Pb levels as a dose. The data from this study indicate a potential link between Cd and testosterone levels, i.e. potential association of Cd exposure with male reproductive health.